Pengaruh Pendekatan Problem Centered Learning (PCL) Terhadap Kemampuan BerpikirKreatif Siswa dalam Pembelajaran Matematika - Eline Yanty Putri Nasution; Asra Nisa; Nur Rusliah (Venn: Journal of Sustainable Innovation on Education, Mathematics and Natural Sciences, 2022)
This study started from the lack of students’ mathematical creative thinking skills in SMPN 4 Kerinci. The Problem Centered Learning (PCL) Approach can improve the students’ creative thinking ability in theory. We interested to investigate the effect of the Problem Centered Learning (PCL) Approach in students’ creative thinking skills through this study. The purpose of this study was to determine the students’ mathematical creative thinking skills in solving triangles and quadrilaterals problems with using Problem Centered Learning (PCL) Approach. This study was quasi experiment research with Post-Test Only Control Group Design. The research sample consisted of the entire population from VII A and VII B grades at SMPN 4 Kerinci. Therefore we use the saturated sample technique where 20 students in VII A grade as experimental class then 20 students in VII B grade as control class. We use the creative thinking test, observation sheet and documentation technique to collect the data. The data were analyzed using the parametric t-test because the data distribution was normal and the sample was come from the homogeny population. The results of this study indicate that students in the experimental class have better creative thinking skills than the control class. The lack of students’ creative thinking ability in the control class was caused by most of students pay less attention to the learning process, did not master the triangle and quadrilateral material and lack ability in developing an idea in solving the given problem.